Profile of mood state on individual and team sports / Faizeatul Ramli - Ramli, Faizeatul (Faculty of Sport Science and Recreation, 2017)
The main purpose of this study was to determine the mean difference between individual and team sports among individual and team sports athletes from Vitro Shah Alam. The participants comprised of male and female athletes age ranged 19 to 24 years old (N=60). Mood states were measured by the Profile of Mood States (POMS) questionnaire that includes six sub-scales, anger, confusion, depression, fatigue, tension and vigor. The questionnaire was distributed to the participants within 30 minutes before the prior competition. In order to analyze data, descriptive statistics (mean, standard deviation), and independent t-test were used. The result indicated that the mean for individual sports participants was higher on vigor (mean=21.23) of POMS in compared with the mean for team sports participants was depression (mean=19.97). However, in result of POMS, using an independent t-test, it was confirmed that mean difference between mood state and both sports were significant with, t (-7.928) = -9.3, P = 0.001 (two-tailed). This represent a very strong effect, d = 16.07.